2021
DOI: 10.1017/ice.2021.351
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship in patients with confirmed coronavirus disease 2019 (COVID-19)

Abstract: 173 hospitalized COVID-19 patients receiving antibiotics were retrospectively assigned to the early or late discontinuation groups. Length of therapy was shorter in the early discontinuation group (3 vs 7 days, p<0.0001). Mortality (14.3% vs 20.7%, p=0.316) and length of stay (7 vs. 9 days, p=0.063) were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“… 1 There is now a trend towards improving antimicrobial stewardship for hospitalized patients with SARS-CoV-2. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“… 1 There is now a trend towards improving antimicrobial stewardship for hospitalized patients with SARS-CoV-2. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…58 Many reports have highlighted that targeted stewardship interventions were effective in reducing antibiotic use among patients infected with SARS-CoV-2. 93,98 ASP efforts during the COVID-19 pandemic have gone far beyond antibiotic management. They have been crucial to assess to emerging treatment regimens for COVID-19, implementing use of remdesivir, dexamethasone, or interleukin-6 inhibitors, and providing expertise and resources to help implement monoclonal antibody treatment and COVID-19 vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…58 Many reports have highlighted that targeted stewardship interventions were effective in reducing antibiotic use among patients infected with SARS-CoV-2. 93 , 98 …”
Section: Discussionmentioning
confidence: 99%
“…Moore et al and Heesom et al conducted single-center trials and observed no difference in mortality in COVID-19 patients when antibiotics were discontinued based on a recommendation from antimicrobial stewardship programs using PCT guidance. 48,49 Moradi et al conducted a multi-site quasi-experimental study describing a pre and post period when the electronic health record began displaying a recommendation to consider discontinuing antibiotics to prescribers if adult patients had a PCT result < 0.25 ng/mL and a positive viral respiratory PCR within 48 hours of each another. This study found a reduction in mean antibiotic days (5.8 vs 8, p <0.001) without a difference in antibiotic restarts after discontinuation.…”
Section: Guideline Recommendations and Management Strategiesmentioning
confidence: 99%
“…Though retrospective data exists in limiting antibiotics in patients with viral CAP, these studies are limited by being single-center and uncontrolled. [48][49][50] There is a need for a standardized clinical and microbiologic approach to assessing risk of bacterial co-infection which should be developed and rigorously tested in a prospective, randomized controlled trial. Ideally, such an approach would be validated in multiple viruses, geographic regions and patient populations, including those who are critically-ill or immunocompromised.…”
Section: Future Directionsmentioning
confidence: 99%